Mind over matter: an exploratory case study of mind-body interventions in the burn unit - Anderson, Abby, author; Schmid, Arlene A., advisor; Atler, Karen E., committee member; Yuma, Paula, committee member (Colorado State University. Libraries, 2019)
Introduction: The aim of this case study was to explore the experience of five patients who participated in mind-body based occupational therapy (MB-OT) while in the burn unit. Individual responses to mind-body practices were assessed and patient perspectives were included to better understand what MB-OT brought to the recovery process.

Methods: This retrospective chart review included five patients admitted to the burn unit. Data were gathered from the electronic medical records (EMRs) to include demographics and burn characteristics, changes in vital signs throughout MB-OT meditation sessions, specifically, and before and after measures on the State-Trait Anxiety Inventory-6 (STAI-6), which was available for two patients. Additional information was obtained from occupational therapy documentation to better understand the unique experience of each patient with the MB-OT intervention. Inductive content analysis occurred within and across subjects to generate induvial and over-arching themes. Results: Patients experienced a reduction in heart rate during seven of the eight MB-OT meditation sessions, while a reduction in respiration rate was seen in four of these sessions. For two patients, STAI-6 measures were available and indicated a reduction in state-anxiety scores after MB-OT. Inductive coding within subjects revealed that patients self-generated a desired focus for MB-OT and perceived that MB-OT supported personal coping. Four themes emerged across documentation of all five patients and included 1) eagerness to explore mind-body practices; 2) feelings of appreciation towards MB-OT; 3) MB-OT provided a sense of calm; 4) MB-OT supported daily occupations in the burn unit.

Conclusion: MB-OT was a client-driven intervention that complemented standard occupational therapy practice in the burn unit. MB-OT has the potential to support patients in coping with everyday aspects of life in the burn unit.
Keywords: burn unit; mind-body; yoga; coping; burn patients; mindfulness